Barefoot capitalism: a solution for India - "Sorman, Guy" (New Delhi, 1989)
The Third World is not the desperate, inert mass that we are so often given to believe in the West: it does in fact think, work and innovate. Guy Sorman shows us the Third World in a new light, as we travel with him to eighteen countries spanning three continents : we move from Egypt to India, Brazil, Korea, Cuba and then to south Africa. With the author, we meet Heads of State, poets, philosophers, economists, the mighty and the meek. And a new definition of the Third World begins to take shape its inhabitants are not so much the victims of adverse natural conditions or imperialist designs as they are of the erroneous policies of their own govemments. What also emerges is that neither short cut formulae nor revo lutionary ideologies are capable of solv ing the problem of widespread poverty. The only solutions are practical solu tions the Green Revolution which eliminated famine in India, agrarian reform in Taiwan and China, the con quest of world markets by Korea - all examples that illustrate how the under developed of our planet became rich in twenty five years.
Keywords: Economics